Effect of Work Environment and Work Motivation on Employee Performance in The Department of Investment and PTSP South Tangerang City - Tias Rindu Putri; Puput Purnamawati; Mesrawati Hulu; Rahmat Levaji; Pantoni Indra (Indonesian Development of Economics and Administration Journal, 2022)
The influence of the work environment and work motivation on employee performance at the investment service and ptsp tangerang south city. What is the influence of the work environment and work motivation on employee performance simultaneously at the Investment Service and PTSP Kota Tangerang Selatan. It is suspected that there is a positive and significant influence between work environment (X1) and work motivation (X2) on employee performance (Y). Based on the table of validity test results above, it is known that most of the statement items in this study are valid as indicated by the value of each statement item having a positive Pearson Correlation value and greater than the rtable value of 0.1865. It can be concluded that the statement items in this study are valid. . The results of multiple linear regression tests on career development and employee motivation variables Y = 1.946+0.343X1+0.618 X2+e. Based on the F statistical test (simultaneous), it can be seen that the calculated F-value is 217.596 > Ftable 3.08 and a significance value of 0.000 <0.05, it can be concluded that Ho is rejected and Ha3 is accepted. This means that the variables of Work Environment and Motivation simultaneously have a significant effect on Employee Performance. The author is very grateful to the Investment Service and PTSP South Tangerang Master of Management Program. Pamulang University which has provided support in writing this journal. The author really hopes that this journal can be useful for students and universities and for the investment Tangerang City.